Moderating effects of religiosity on the predictors of happiness among postgraduate students in Malaysian public universities - Abu Rahim, Mohd Amirul Rafiq (2015)
There are few numbers of empirical studies on happiness and most of the studies evaluate the level on happiness according to economic perspective. The existing body of knowledge on the predictors of happiness is limited to western perspective and cultures and with inclusive findings. The overall purposes of the thesis were to identify factors influencing to happiness as well as to examine the moderating effect of religiosity on the happiness predictors among local postgraduates in Malaysian public universities. Sample for this study was 525 postgraduates from four selected public university in Malaysia. Fieldwork survey has been conducted in 2013. A structured questionnaire were distributed to the selected sample. A Rasch rating scale model was utilized using Winstep software to each constructs which are life satisfaction, intrinsic and extrinsic religiosity, and happiness scale in order to investigate the measurement properties and to determine the equivalence of the item level across each construct. Person and item reliability for each construct for the study conform satisfactorily to the Rasch model. A Rasch model also been used in order to identify the status of happiness, life satisfaction, as well as religiosity among postgraduates. The analysis revealed that postgraduates are generally having low happiness, moderate to high life satisfaction, high intrinsic religiosity and but low extrinsic religiosity. The summated logit score of Rasch were used in order to identify the difference of happiness status among postgraduates across gender, ethnicity, level of study and religion. One-way ANOVA and independent sample t-test was utilized to investigate those difference among postgraduates happiness. Results suggest that there is no difference in each group level at all tested variables. It shows that the level of happiness among local postgraduates in Malaysian public universities are similar. A multiple regression analysis and the moderated hierarchical regression analysis were used to test hypothesis of influencing predictors in postgraduates happiness. Using the multiple regression analysis, a significant model emerged, and variables of life satisfaction were found to not significantly influencing postgraduates happiness. The other demographic factors which are gender, ethnicity,religion and level of study were significantly influence the postgraduates’ happiness. Besides, intrinsic religiosity was found to influence the postgraduates happiness while extrinsic religiosity are not. Lastly, a hierarchical regression analysis was conducted to examine the moderating effects of religiosity on the predictors of happiness. The analysis revealed that interaction of both intrinsic and extrinsic religiosity are significantly moderate the relationship between the predictors of postgraduates happiness in Malaysian public universities. Based on these findings, the study recommended that future a broader context and scope of people happiness could be investigated. A qualitative study should also be undertaken in future research. Through a qualitative design, richer picture of other related variables that might influence peoples happiness could be identified.